IFRS compliance, corporate governance and financial reporting quality of GSE-listed non-financial firms - Deborah Esi Gyanba Mbir; Otuo Serebour Agyemang; George Tackie; Mac Junior Abeka (Cogent Business & Management, 2020)
The adoption of International financial reporting standards (IFRS) has been presented in several empirical literature as a factor that could improve the quality of financial reports. However, Ghana has not attained the desired levels of financial reporting quality after the adoption of IFRS. Literature reveals that lack of proper enforcement of these high-quality standards may result in limited compliance and will undermine the effectiveness of these standards in terms of attaining high-quality financial reports. This study therefore argues that the relationship between IFRS compliance and reporting quality revolves around some enforcement mechanisms like corporate governance structures. In view of that, by using random effect estimation technique, this study examined the role of corporate governance in the relationship between IFRS compliance and the reporting quality of firms listed on the Ghana Stock Exchange (GSE). The study found that the right corporate governance mechanisms will enhance the positive effect of IFRS compliance on reporting quality. This study further recommends that to gain an appreciable level of public confidence in the annual reports of firms listed on the GSE, the audit committee’s independence and the board’s independence should be strengthened to ensure that management does not only adopt IFRS, but that the standards are actually complied with.